Case Report: Fusarium falciforme pericardial and sternal wound infection following orthotopic heart transplantation - Jeffrey Rodgers; Morgan Hill; Sanford Zeigler (Frontiers in Cardiovascular Medicine)
Fusarium, a genus of soil and vegetation-based fungi, is a rare cause of infections in immunocompromised individuals, including transplant recipients. In this case, we describe successful treatment of Fusarium falciforme mediastinitis in the recipient of an orthotopic heart transplant. Treatment included multiple courses of combination antibiotic and antifungal therapy several surgical debridements, continuous mediastinal irrigation with antifungal agents, and staged closure with an omental flap. This is the first report describing successful eradication of fusarium sp. mediastinitis and provides a template for treating complex cases of mediastinitis and osteomyelitis.